MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Nano-island Cu–Cu2O heterojunctions: Synergistic electroreduction of bromate at mixed-valence perimeters - Yu Chu; Junjie Li; Huihuan Lin; Binyu Ma; Zhipeng Luo; Yue Cheng; Xin Yu; Huabin Zeng (Journal of Water Process Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Fine-scale post-fire forest recovery patterns and compound drivers in Taiwan’s high-mountain national parks - Chu-Chia Kuo; Yu-Ling Liu; Cheng-Tao Lin (Forest Ecology and Management, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Carbon nanotube/two-dimensional metal–organic framework composites with enhanced thermoelectric performances for thermoelectric generators - Cheng-Yuan Lin; Jhe-Wei Chang; Meng-Hao Lin; Kuan-Chu Wu; Shao-Huan Hong; Jhih-Min Lin; Chung-Wei Kung; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Evidence for a command neuron controlling calling song in the cricket Gryllus assimilis - Chu-Cheng Lin; Berthold Hedwig (Journal of Insect Physiology, 2025)

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Removal of single and multi-heavy metals from piggery digestate by the electric field-microalgae system: Influences, kinetics and mechanisms - Xiaosong Tian; Min Wang; Xing Liao; Shiyu Chu; Haixiang Cheng; Xiaoai Lin; Longzao Luo (Algal Research, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Safety analysis code development and validation for lead-cooled fast reactor with helical coiled once-through steam generator - Jiaxin Zhang; Chenglong Wang; Wenxi Tian; G.H Su; Suizheng Qiu; Lin Xian; Kun Cheng; Xiao Chu; Shiying Wei; Guo Chen (Annals of Nuclear Energy, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Novel chitosan-modified biochar prepared from a Chinese herb residue for multiple heavy metals removal: Characterization, performance and mechanism - Chengjiu Wang; Jixu Qiao; Jiandan Yuan; Zhentao Tang; Tianzhe Chu; Ruifeng Lin; Hongting Wen; Chuan Zheng; Hulan Chen; Haijiao Xie; Cheng Peng; Yuzhu Tan (Bioresource Technology, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Ultralow-Concentration (0.1M) Electrolyte for stable bulk alloy (Sn, Bi) anode in Sodium-ion battery via Regulating Anions Structure - Changting Chu; Lin Zhou; Yong Cheng; Xuxu Wang; Limin Chang; Ping Nie; Chunli Wang; Limin Wang (Chemical Engineering Journal, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Oral and inhalation bioaccessibility of mercury in contaminated soils and potential health risk to the kidneys and neurodevelopment of children in Taiwan - Ying-Lin Wang; Ming-Chien Mark Tsou; Li-Chi Lai; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Geochemistry and Health, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Plastic film-mulched ridges and straw-mulched furrows increase soil carbon sequestration and net ecosystem economic benefit in a wheat-maize rotation - Xiaoqi Luo; Cheng Li; Nanping Lin; Naijiang Wang; Xiaosheng Chu; Hao Feng; Haixin Chen (Agriculture, Ecosystems & Environment, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Groundwater vulnerability assessment of shallow aquifer in the South Texas sand sheet using a GIS-based DRASTIC model - Syed Istiyak Ahmed; Chu-Lin Cheng; Juan Gonzalez; James J. Kang; Jungseok Ho; Leslie Soto-Sanchez (Modeling Earth Systems and Environment, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Effect of starvation and refeeding on reactive oxygen species, autophagy and oxidative stress in Chinese perch ( Siniperca chuatsi ) muscle growth - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xin Zhu; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2022)
In skeletal muscle, autophagy regulates the development and growth of muscle fibres and maintains the normal muscle metabolism. Under starvation and refeeding conditions, the effect of reactive oxygen species (ROS) levels on skeletal muscle autophagy is still unclear, although the excessive accumulation of ROS has been shown to increase autophagy in cells. The purpose of this study was to explore the effects of starvation and diet after starvation on the autophagy of adult Chinese perch muscle, and to determine the level of ROS in the muscle. We performed zero (Normal control), three and seven starvation treatments on adult Chinese perch, and returned to normal feeding for 3 days after starvation for 7 days. In the muscles of the adult Chinese perch muscle after 3 days of starvation, the autophagy marker protein LC3 and the number of autophagosomes remained basically the same as in the normal feeding situation. However, on starvation for 7 days, the mitochondrial autophagy was sensitive and the number of autophagosomes increased, but the antioxidant‐related molecules (malondialdehyde, catalase, glutathione S‐transferase, glutathione and anti‐superoxide anion) decreased and the accumulation of ROS was obvious. In addition, the extended starvation time also increased the level of LC3 protein. However, by refeeding after starvation this nutritional stress resulted in a decrease in ROS levels and a partial restoration of antioxidant enzyme activity. Our data show that in the adult Chinese perch muscle, starvation could reduce the antioxidant activity through the accumulation of ROS, and that the number of autophagosomes continues to increase. Refeeding after starvation could effectively compensate for the level of ROS, and restore the mRNA abundance of antioxidant genes and the activity of antioxidant enzymes to reduce autophagy and improve feed efficiency. Further research should optimize starvation conditions to reduce autophagy in muscles and maintain normal muscle metabolism.

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Lesions of abdominal connectives reveal a conserved organization of the calling song central pattern generator (CPG) network in different cricket species - Chu-Cheng Lin; Berthold Hedwig (Journal of Comparative Physiology A, 2021)
Although crickets move their front wings for sound production, the abdominal ganglia house the network of the singing central pattern generator. We compared the effects of specific lesions to the connectives of the abdominal ganglion chain on calling song activity in four different species of crickets, generating very different pulse patterns in their calling songs. In all species, singing activity was abolished after the connectives between the metathoracic ganglion complex and the first abdominal ganglion A3 were severed. The song structure was lost and males generated only single sound pulses when connectives between A3 and A4 were cut. Severing connectives between A4 and A5 had no effect in the trilling species, it led to an extension of chirps in a chirping species and to a loss of the phrase structure in two Teleogryllus species. Cutting the connectives between A5 and A6 caused no or minor changes in singing activity. In spite of the species-specific pulse patterns of calling songs, our data indicate a conserved organisation of the calling song motor pattern generating network. The generation of pulses is controlled by ganglia A3 and A4 while A4 and A5 provide the timing information for the chirp and/or phrase structure of the song.

MiRNAs-Modulation of Nrf2 Signaling Networks in Regulation Oxidative Stress of Chinese Perch Skeletal Muscle After Fasting Treatment - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xinhong Guo; Wuying Chu; Jianshe Zhang; Xuanming Liu (Marine Biotechnology, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Nr1d1 affects autophagy in the skeletal muscles of juvenile Nile tilapia by regulating the rhythmic expression of autophagy-related genes - Ping Wu; Jia Cheng; Lin Chen; Jing Xiang; Yaxiong Pan; Yongzhan Zhang; Tao Zheng; Naiyuan Liu; Wuying Chu; Jianshe Zhang (Fish Physiology and Biochemistry, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

Distribution of mercury and methylmercury in surface water and surface sediment of river, irrigation canal, reservoir, and wetland in Taiwan - Ying-Lin Wang; Meng-Der Fang; Ling-Chu Chien; Chu-Ching Lin; Hsing-Cheng Hsi (Environmental Science and Pollution Research, 2019)

Polymer translocation through a hairy channel mimicking the inner plug of a nuclear pore complex - Chibin Zhang; Zhiwei Cheng; Xiaohui Lin; Wenquan Chu (European Biophysics Journal, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

A new design method for extracorporeal high-intensity focused ultrasound annular array - Gin-Shin Chen; Yu-Cheng Lin; Chu-Chiang Chen (Medical & Biological Engineering & Computing, 2015)

High seroprevalence of human herpesvirus type 8 infection in males with advanced lung carcinoma - Cheng-Chuan Su; Chun-Liang Lai; Shih-Ming Tsao; Ming-Nan Lin; Tang-Yuan Chu (Medical Microbiology and Immunology, 2015)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Reply to: Comment on ‘neutron imaging reveals internal plant water dynamics’ - Jeffrey M. Warren; Hassina Bilheux; Chu-Lin Cheng; Edmund Perfect (Plant and Soil, 2013)

Neutron imaging reveals internal plant water dynamics - Jeffrey M. Warren; Hassina Bilheux; Misun Kang; Sophie Voisin; Chu-Lin Cheng; Juske Horita; Edmund Perfect (Plant and Soil, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Role of Diverse Non-Systemic Fungal Endophytes in Plant Performance and Response to Stress: Progress and Approaches - Zhi-lin Yuan; Chu-long Zhang; Fu-cheng Lin (Journal of Plant Growth Regulation, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Dry deposition study by using dry deposition plate and water surface sampler in Shalu, central Taiwan - Chia-Chun Chu; Guor-Cheng Fang; Jhy-Cherng Chen; I-Lin Yang (Environmental Monitoring and Assessment, 2008)

Seasonal change and correlation with environmental parameters for 2-MIB in Feng-Shen Reservoir, Taiwan - Shu-Chu Tung; Tsair-Fuh Lin; Feng-Cheng Yang; Chia-Lin Liu (Environmental Monitoring and Assessment, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)